IDENTIFIKASI PARASIT IKAN BANDENG (Chanos chanos Forskal) YANG DIBUDIDAYAKAN SECARA TRADISIONAL DI TAMBAK DESA BADARAI, KLETEK DAN SUAI KABUPATEN MALAKA PROVINSI NUSA TENGGARA TIMUR (NTT) - Yulianus Seran; Yuliana Salosso; Ridwan Tobuku (Jurnal Akuatik, 2019)
This research aims to measure the prevalence, intensity and species of parasite that infected Milk fish that cultured in traditional fishpond in Malaka Regency, Province of East Nusa Tenggara (NTT). Ten individuals of Milk fish sample had taken from each traditional tambak of Badarai village, Kletek Village and Suai Village. The identification of parasite used microscope. The result showed that there were two species of parasites found namely Actinocleidus sp and Gyrodactilus sp, class of ectoparasite. Prevalence percentage of Actinocleidus sp from sample of Badarai’s fishpond is 30% and Gyrodactilus sp 10%, there were not parasite found for fishpond of kletek and Suai villages therefore the prevalence percentage is 0%. Intensity percentage of Actinocleidus sp is 3 ind/fish and Gyrodactilus sp 2 ind/fish for Badarai’s fishpond.Whereas prevalence percentage is 0% for tambak of Suai and Kletek Villages. Keywords: Identification, parasite, Milk Fish, prevalence, intensity.